New moon - Meyer, Stephenie, 1973- (Little, Brown and Company, 2006)
When the Cullens, including her beloved Edward, leave Forks rather than risk revealing that they are vampires, it is almost too much for eighteen-year-old Bella to bear, but she finds solace in her friend Jacob until he is drawn into a "cult" and changes in terrible ways.